Iš Lietuvos KP spaudos leidimo Vokietijoje 1920–1933 metais istorijos - Zaveckienė, Žiedūnė (Knygotyra, 1982)
The works of underground Lithuanian Party, the Young Communist Leaque and other revolutionary organizations were often publicated in Germany, especially in 1928–1933 years. The Lithuanian Communist’s press was printed in Köningsberg, Tilzit (Publishing house Mauderode), Berlin. There had been published about 100 books and brochure, 230 numbers of periodicals and many appeals in Lithuanian, Russian, German, Jewish. Representatives of Lithuanian Communist Party, German Communists and non-Party people W. Sshutz, M. Laborius, R. Nedermeyer, A. Schatat-Augat and many others had taken part in this difficult and dangerous work and later become victims of fashist terrorism. Publication of Lithuanian Communist’s works in Germany afford striking evidence of international solidarity and maintenance of revolutionary movement by working people in various countries.